The Effect of Giving Nanoherbal of Biwa (Eriobotrya japonica (Thunb.) Lindl. (Thunb.) Lindl.) Leaf on the Quality and Quantity of Spermatozoa And Microstructure in Diabetes Rat (Rattus norvegicus) Induced by Alloxan - Ilyas, Syafruddin (International Journal of Ecophysiology, 2022)
One of causes in decreasing quantity and quality of spermatozoon is disease. Increased blood glucose levels can trigger demage of spermatogenesis in the testes, thereby reducing spermatozoa production. Biwa leaves (Eriobotrya japonica (Thunb.) Lindl.) contain triterpenes which are expected to overcome blood glucose levels and quantity of spermatozoa in the cauda epididymis. To investigate this problem, an experimental test of nano herbal of biwa leaves was carried out in a rat model (Rattus norvegicus) diabet. There are five treatments and six replications, it was found that the best dose of 500 mg/kg body weight could improve spermatogenesis so that the number of rat spermatozoa remained normal. It was concluded that nano herbal of biwa leaves can be used as an alternative drug to maintain fertility as seen from spermatogenesis and the number of spermatozoa. The result is analyzed by ANOVA test and further by Post-Hoc-Test (Duncan). The result show the significant differences (p<0,05) to quantity and quality of spermatozoon of adult white male mouse (Rattus norvegicus).